(untitled) (Al-Academy, 2023)
This research deals with the perceived and the imagined in the texts of Yusef Al-Sayegh, considering language as the most important source in literature and theatrical criticism, and given the importance of the subject, the researcher monitored many philosophical and psychological opinions and theories related to (the perceived and the imagined), and they were discussed and their compatibility with the Iraqi theatrical t As for the second chapter, where (the theoretical framework), it included two topics, and the first topic was about the concept of the perceived and the imagined, and the second topic was about Youssef Al-Sayegh and the structure of the theatrical text.In the third chapter, where (research procedures), the researcher analyzed the text of the play (Desdemona) by its author (Youssef Al-Sayegh), and the researcher intentionally chose his sample by adopting the descriptive analytical approach.ext. The research consisted of the following:In the first chapter where (the methodological framework) that includes the problem of research and identifying the most important obstacles (the perceived and the imaginary) and their necessity in the Iraqi theatrical text, this chapter also included the temporal, spatial and objective limits of the research, and then concluded The most important terms used in the research have been separated.In the fourth chapter, the researcher (discussed the results of the analysis) according to the objectives of the research, as he found that the Iraqi playwright can replace a number of words and sentences to produce the same meanings that the idea of his text aims for from a different text, as well as the possibility of injecting interpretable symbols ( perceived and imagined) In any play, it enables the recipient to receive it and remove ambiguity and ambiguity, if any, and then the researcher reached the conclusions and found that the production of meaning is easy for the recipient if the author succeeds in using the elements of the text in a proper use, just as the Iraqi recipient (the reader) simulates the forms (perceived and imagined). Allah) in correspondence through its symbols and meanings, and it is one of the tasks entrusted to the author of the theatrical text, and then the researcher confirmed the recommendations and proposals.